2011
DOI: 10.1093/oep/gpr050
|View full text |Cite
|
Sign up to set email alerts
|

Inequality and the import demand function

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 49 publications
0
26
1
Order By: Relevance
“…The estimated results indicated that volume of imports, domestic real activity and relative prices are not integrated. Adam, Katsimi and Moutos (2012) obtained data of 36 countries to examine the validity of import demand function in the presence of income inequality and concluded that income inequality impacts import demand. Income inequality increases the import demand in high-income countries but decreases it in low-income countries.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The estimated results indicated that volume of imports, domestic real activity and relative prices are not integrated. Adam, Katsimi and Moutos (2012) obtained data of 36 countries to examine the validity of import demand function in the presence of income inequality and concluded that income inequality impacts import demand. Income inequality increases the import demand in high-income countries but decreases it in low-income countries.…”
Section: Review Of Literaturementioning
confidence: 99%
“…It is necessary to discuss further the effects on current accounts of income inequality and demographic structure. Although plenty of the literature attempts to clarify the influence of trade on inequality, only a few studies have recently emerged to explore the opposite chain of causality: the impact of inequality on trade (Adam et al., 2012; Zweimüller et al, 2018). Our estimation intends to generate some insights into potential links running from income inequality to the strategy of export‐for‐growth in surplus countries (reflected by Z ↑) and to the practice of import‐for‐spending in deficit countries (embodied by X ↑ and Z ↓).…”
Section: Estimation Resultsmentioning
confidence: 99%
“…Thus, there could be endogeneity between institutional ownership and stock volatility, and an instrumental variable treatment is thus required to handle this potential problem. For this purpose and following the literature, this paper simply uses the lagged value of a suspected endogenous regressor in a random effects world (Adam, Katsimi, & Moutos, ). To check the robustness of the results, an HT estimator is used as an instrumental variable technique, which includes both the between and within variations of strictly exogenous variables as instruments for the time‐invariant regressors that are correlated with individual effects (Baltagi, Bresson, & Pirotte, ).…”
Section: Methodsmentioning
confidence: 99%
“…potential problem. For this purpose and following the literature, this paper simply uses the lagged value of a suspected endogenous regressor in a random effects world (Adam, Katsimi, & Moutos, 2012 1) shows that multicollinearity is not a serious problem in the data.…”
Section: Literature Reviewmentioning
confidence: 99%